Corrosion-resistant marine corrosion-resistant composite coating and preparation process thereof

By using modified nano zinc oxide, carbon nanotubes, graphene fillers and self-extracted antifoulants in marine anticorrosion coatings, the problems of poor anticorrosion performance and environmental pollution of existing anticorrosion coatings are solved, and more efficient anticorrosion and prevention are achieved Dirty effect.

CN119410232AInactive Publication Date: 2025-02-11WUXI CHANGCHUAN MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411871995.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anticorrosion coatings have poor anticorrosion performance in marine environments and are prone to environmental pollution.

Method used

A corrosion-resistant marine anti-corrosion composite coating is adopted, including corrosion inhibitors, epoxy resins, inactive diluents, curing agents, homemade modified nano zinc oxide fillers, homemade modified carbon nanotube fillers, homemade modified graphene fillers and self-extract antifouling agents, and improve the stability and dispersion of the coating by using modified fillers and antifouling agents, and enhance anti-corrosion and antifouling properties.

Benefits of technology

The coating has better stability and dispersion, significantly improves corrosion and anti-fouling properties, extends service life, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410232A_ABST
    Figure CN119410232A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant marine corrosion-resistant composite coating and a preparation process thereof, and belongs to the technical field of corrosion-resistant coatings. The coating comprises the following components in parts by weight: 5-8 parts of a corrosion inhibitor, 90-100 parts of epoxy resin, 10-20 parts of a non-active diluent, 45-50 parts of a curing agent, 2-6 parts of a self-made modified nano zinc oxide filler, 0.5-1.5 parts of a self-made modified carbon nanotube filler, 5-8 parts of a self-made modified graphene filler and 1-2 parts of a self-extraction antifouling agent. The corrosion-resistant marine corrosion-resistant composite coating is prepared by adding self-made modified nano zinc oxide, self-made modified carbon nanotubes and self-made modified graphene on the basis of a corrosion-resistant coating, so that the prepared corresponding filler has better stability and dispersity in a coating system; meanwhile, the prepared anti-corrosion composite coating has corrosion resistance and corrosion resistance, has the characteristics of good toughness, strong adhesive force, good water resistance, high hardness and the like, and has better antifouling and corrosion resistance than the existing anti-corrosion coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a corrosion-resistant marine anti-corrosion composite coating and a preparation process thereof. Background Art

[0002] Due to the particularity of the seawater environment, the biofouling and corrosion of marine engineering materials has become one of the focal issues of worldwide concern. Extensive research has been conducted at home and abroad on the corrosion of marine engineering materials. One of the methods is to prevent it by applying anti-corrosion coatings, which has achieved good application results.

[0003] Marine anti-corrosion requires high-quality coatings, which usually require a protection period of at least 10 years, and belongs to the field of heavy-duty anti-corrosion. Heavy-duty anti-corrosion coatings refer to coatings that can be used in harsh corrosive environments and have a long service life. To a certain extent, the development level of heavy-duty anti-corrosion coatings marks the development level of a country's anti-corrosion coatings and even the level of scientific and technological development of a country. The development and research cycle of marine anti-corrosion coatings is long, the investment is large, the technical difficulty is high, and the risk is high. Therefore, the research and development of marine anti-corrosion coatings abroad is mainly concentrated in large companies with strong strength or departments supported by the government. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant marine anti-corrosion composite coating. Another purpose of the present invention is to provide a preparation process of a corrosion-resistant marine anti-corrosion composite coating, aiming to solve the problems of poor anti-corrosion performance of existing anti-corrosion coatings and easy environmental pollution.

[0005] In order to solve the above technical problems, the present invention provides a corrosion-resistant marine anti-corrosion composite coating, comprising 5-8 parts of corrosion inhibitor, 90-100 parts of epoxy resin, 10-20 parts of inactive diluent and 45-50 parts of curing agent in parts by weight. The composite coating also comprises 2-6 parts of homemade modified nano zinc oxide filler, 0.5-1.5 parts of homemade modified carbon nanotube filler, 5-8 parts of homemade modified graphene filler and 1-2 parts of self-extractable antifouling agent in parts by weight.

[0006] Preferably, the preparation method of the homemade modified nano zinc oxide filler is: add n-butanol with a mass 6 times that of nano zinc oxide and isopropyl tri(dioctyl pyrophosphoryl) titanate with a mass 0.06 times that of nano zinc oxide into a reaction bottle, stir and mix for 5 minutes, add nano zinc oxide, heat to 40°C and stir for 2 hours, filter, vacuum dry the filter cake at 60°C to constant weight, grind and pass through a 2000 mesh sieve to obtain the filler.

[0007] The preparation method of the homemade modified carbon nanotube filler is as follows: concentrated sulfuric acid with a mass of 100 times the mass of the carbon nanotubes and concentrated nitric acid with a mass of 200 times the mass of the carbon nanotubes are added to the reaction bottle in sequence, stirred and mixed evenly, then the carbon nanotubes are added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times the mass of the carbon nanotubes and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated carbon nanotubes; another reaction bottle is taken, purified water with a weight of 5 times the weight of the carbon nanotubes and γ-aminopropyltriethoxysilane with a weight of 0.08 times the weight of the carbon nanotubes are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated carbon nanotubes are added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, vacuum dried at 40°C to constant weight, ground and sieved through a 2000-mesh sieve.

[0008] The preparation method of the homemade modified graphene filler is as follows: concentrated sulfuric acid with a mass of 100 times the mass of graphene and concentrated nitric acid with a mass of 200 times the mass of graphene are added to the reaction bottle in sequence, stirred and mixed evenly, then graphene is added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times the mass of graphene and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated graphene; another reaction bottle is taken, purified water with a weight of 5 times the weight of graphene and γ-aminopropyltriethoxysilane with a weight of 0.08 times the weight of graphene are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated graphene is added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried at 40°C in vacuum to constant weight, ground and sieved through a 2000 mesh sieve.

[0009] Preferably, the corrosion inhibitor is a powder mixture of sodium nitrite and potassium dihydrogen phosphate, with sodium nitrite: potassium dihydrogen phosphate W / W=1 / 1.

[0010] Preferably, the epoxy resin is E44 bisphenol A type epoxy resin.

[0011] Preferably, the preparation method of the self-extractable antifouling agent is: the dried shasha hot pepper is crushed by a crusher, added into ethanol with a volume 5 times the weight of the shasha hot pepper, heated to an internal temperature of 50°C, stirred and extracted for 12 hours, filtered, and the filtrate is concentrated under reduced pressure to dryness.

[0012] Preferably, the inactive diluent is a mixture of n-butanol and diethylene glycol dimethyl ether, with n-butanol: diethylene glycol dimethyl ether W / W=6:4.

[0013] Preferably, the curing agent is 650 polyamide curing agent (amine value: 220±20).

[0014] A preparation process of a corrosion-resistant marine anticorrosive composite coating comprises the following steps: S1. Add the inactive diluent to the reaction bottle in order according to the mixing ratio, add the corrosion inhibitor and the self-extractable antifouling agent in order under stirring, and heat to 50° C. to dissolve, to obtain a mixture 1; S2, adding the homemade modified nano zinc oxide filler, the homemade modified carbon nanotube filler and the homemade modified graphene filler to the mixed material 1 obtained in step S1 under stirring, and stirring for 10 minutes to make the mixture evenly dispersed to obtain a mixed material 2; S3, slowly adding the mixture 2 obtained in step S2 into E44 bisphenol A epoxy resin under stirring, stirring and mixing for 30 minutes to obtain a mixture 3; S4, adding a curing agent to the mixture 3 obtained in step S3 under vigorous stirring, mixing evenly, and standing to mature.

[0015] Preferably, the standing and aging time in step S4 is 40 minutes.

[0016] The beneficial effects of the present invention are as follows: the present invention provides a corrosion-resistant marine anticorrosive composite coating, in which the filler has better stability and dispersibility in the coating system after modification, and the added self-extractable antifouling agent has a repelling effect on marine organisms, reducing the surface aggregation of marine organisms, and at the same time, the prepared anticorrosive composite coating has corrosion resistance and anticorrosion properties, and has the characteristics of good toughness, strong adhesion, good water resistance, high hardness, etc., and its antifouling and anticorrosion properties exceed those of existing anticorrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the surface modification mechanism of titanate coupling agent molecules and zinc oxide.

[0018] Figure 2 This is the infrared spectrum of nano zinc oxide before and after modification.

[0019] Figure 3 Shown are the XRD patterns of nano zinc oxide before and after modification.

[0020] Figure 4 This is a curve chart showing the relationship between the amount of modified nano zinc oxide added and the antibacterial rate of the coating.

[0021] Figure 5 Schematic diagram of the modification mechanism of carbon nanotubes.

[0022] Figure 6 Infrared spectra of carbon nanotubes before and after modification and hydroxylated carbon nanotubes.

[0023] Figure 7 Infrared spectra of graphene before and after modification.

[0024] Figure 8 The corresponding graphene antibacterial rate diagram. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1 Preparation of homemade modified nano zinc oxide filler: Add n-butanol (6 times the mass of nano zinc oxide) and isopropyl tri(dioctyl pyrophosphoryl) titanate (0.06 times the mass of nano zinc oxide) into the reaction bottle, stir and mix for 5 minutes, add nano zinc oxide, heat to 40°C and stir for 2 hours, filter, vacuum dry the filter cake at 60°C to constant weight, grind and pass through a 2000 mesh sieve.

[0027] Preparation of homemade modified carbon nanotube filler: Concentrated sulfuric acid with a mass of 100 times that of the carbon nanotubes and concentrated nitric acid with a mass of 200 times that of the carbon nanotubes are added to the reaction bottle in sequence, stirred and mixed evenly, then the carbon nanotubes are added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of the carbon nanotubes and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH = 7, and vacuum dried at 60°C to obtain hydroxylated carbon nanotubes; another reaction bottle is taken, purified water with a weight of 5 times that of the carbon nanotubes and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of the carbon nanotubes are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated carbon nanotubes are added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried at 40°C in vacuum to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0028] Preparation of homemade modified graphene filler: Concentrated sulfuric acid with a mass of 100 times that of graphene and concentrated nitric acid with a mass of 200 times that of graphene are added to the reaction bottle in sequence, stirred and mixed evenly, then graphene is added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of graphene and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated graphene; another reaction bottle is taken, purified water with a weight of 5 times that of graphene and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of graphene are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated graphene is added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried in vacuum at 40°C to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0029] Self-extractable antifouling agent preparation: The dried shabu shabu chili pepper was crushed in a crusher, added into ethanol with a volume 5 times the weight of the shabu shabu chili pepper, heated to an internal temperature of 50°C, stirred and extracted for 12 hours, filtered, and the filtrate was concentrated under reduced pressure to dryness.

[0030] Preparation of corrosion-resistant marine anticorrosive composite coatings: Add 60g of n-butanol and 40g of dimethyl ether of dioxalate to the reaction flask in sequence, add 25g of sodium nitrite, 25g of potassium dihydrogen phosphate powder and 10g of self-extractable antifouling agent in sequence under stirring, heat to 50°C to dissolve, and obtain mixture 1; add 20g of homemade modified nano zinc oxide filler, 5g of homemade modified carbon nanotube filler and 50g of homemade modified graphene filler to mixture 1 under stirring, stir for 10 minutes to evenly disperse it to obtain mixture 2; slowly add mixture 2 to 900g of E44 bisphenol A epoxy resin under stirring, stir and mix for 30 minutes to obtain mixture 3; add 450g of 650 polyamide curing agent to mixture 3 under vigorous stirring, mix evenly, and let stand and mature for 40 minutes to obtain.

[0031] Example 2 Preparation of homemade modified nano zinc oxide filler: Add n-butanol (6 times the mass of nano zinc oxide) and isopropyl tri(dioctyl pyrophosphoryl) titanate (0.06 times the mass of nano zinc oxide) into the reaction bottle, stir and mix for 5 minutes, add nano zinc oxide, heat to 40°C and stir for 2 hours, filter, vacuum dry the filter cake at 60°C to constant weight, grind and pass through a 2000 mesh sieve.

[0032] Preparation of homemade modified carbon nanotube filler: Concentrated sulfuric acid with a mass of 100 times that of the carbon nanotubes and concentrated nitric acid with a mass of 200 times that of the carbon nanotubes are added to the reaction bottle in sequence, stirred and mixed evenly, then the carbon nanotubes are added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of the carbon nanotubes and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH = 7, and vacuum dried at 60°C to obtain hydroxylated carbon nanotubes; another reaction bottle is taken, purified water with a weight of 5 times that of the carbon nanotubes and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of the carbon nanotubes are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated carbon nanotubes are added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried at 40°C in vacuum to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0033] Preparation of homemade modified graphene filler: Concentrated sulfuric acid with a mass of 100 times that of graphene and concentrated nitric acid with a mass of 200 times that of graphene are added to the reaction bottle in sequence, stirred and mixed evenly, then graphene is added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of graphene and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated graphene; another reaction bottle is taken, purified water with a weight of 5 times that of graphene and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of graphene are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated graphene is added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried in vacuum at 40°C to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0034] Self-extractable antifouling agent preparation: The dried shabu shabu chili pepper was crushed in a crusher, added into ethanol with a volume 5 times the weight of the shabu shabu chili pepper, heated to an internal temperature of 50°C, stirred and extracted for 12 hours, filtered, and the filtrate was concentrated under reduced pressure to dryness.

[0035] Preparation of corrosion-resistant marine anticorrosive composite coatings: 90 g of n-butanol and 60 g of dimethyl ether of dioxalate were added to the reaction flask in sequence, and 32.5 g of sodium nitrite, 32.5 g of potassium dihydrogen phosphate powder and 15 g of self-extractable antifouling agent were added in sequence under stirring, and the mixture was heated to 50°C for dissolution to obtain a mixture 1; 40 g of a homemade modified nano zinc oxide filler, 10 g of a homemade modified carbon nanotube filler and 65 g of a homemade modified graphene filler were added to the mixture 1 under stirring, and the mixture was stirred for 10 min to be evenly dispersed to obtain a mixture 2; the mixture 2 was slowly added to 950 g of E44 bisphenol A epoxy resin under stirring, and the mixture was stirred for 30 min to obtain a mixture 3; 475 g of 650 polyamide curing agent was added to the mixture 3 under vigorous stirring, the mixture was evenly mixed, and the mixture was allowed to stand and mature for 40 min to obtain a mixture 3.

[0036] Example 3 Preparation of homemade modified nano zinc oxide filler: Add n-butanol (6 times the mass of nano zinc oxide) and isopropyl tri(dioctyl pyrophosphoryl) titanate (0.06 times the mass of nano zinc oxide) into the reaction bottle, stir and mix for 5 minutes, add nano zinc oxide, heat to 40°C and stir for 2 hours, filter, vacuum dry the filter cake at 60°C to constant weight, grind and pass through a 2000 mesh sieve.

[0037] Preparation of homemade modified carbon nanotube filler: Concentrated sulfuric acid with a mass of 100 times that of the carbon nanotubes and concentrated nitric acid with a mass of 200 times that of the carbon nanotubes are added to the reaction bottle in sequence, stirred and mixed evenly, then the carbon nanotubes are added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of the carbon nanotubes and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH = 7, and vacuum dried at 60°C to obtain hydroxylated carbon nanotubes; another reaction bottle is taken, purified water with a weight of 5 times that of the carbon nanotubes and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of the carbon nanotubes are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated carbon nanotubes are added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried at 40°C in vacuum to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0038] Preparation of homemade modified graphene filler: Concentrated sulfuric acid with a mass of 100 times that of graphene and concentrated nitric acid with a mass of 200 times that of graphene are added to the reaction bottle in sequence, stirred and mixed evenly, then graphene is added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of graphene and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated graphene; another reaction bottle is taken, purified water with a weight of 5 times that of graphene and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of graphene are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated graphene is added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried in vacuum at 40°C to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

[0039] Self-extractable antifouling agent preparation: The dried shabu shabu chili pepper was crushed in a crusher, added into ethanol with a volume 5 times the weight of the shabu shabu chili pepper, heated to an internal temperature of 50°C, stirred and extracted for 12 hours, filtered, and the filtrate was concentrated under reduced pressure to dryness.

[0040] Preparation of corrosion-resistant marine anticorrosive composite coatings: 120g of n-butanol and 80g of dimethyl ether of dioxalate were added to the reaction flask in sequence, and 40g of sodium nitrite, 40g of potassium dihydrogen phosphate powder and 20g of self-extractable antifouling agent were added in sequence under stirring, and the mixture was heated to 50°C for dissolution to obtain a mixture 1; 60g of homemade modified nano zinc oxide filler, 15g of homemade modified carbon nanotube filler and 80g of homemade modified graphene filler were added to the mixture 1 under stirring, and the mixture was stirred for 10min to be evenly dispersed to obtain a mixture 2; the mixture 2 was slowly added to 1000g of E44 bisphenol A epoxy resin under stirring, and the mixture was stirred for 30min to obtain a mixture 3; 500g of 650 polyamide curing agent was added to the mixture 3 under vigorous stirring, mixed evenly, and allowed to stand and mature for 40min to obtain a mixture.

[0041] Comparative Example 1 Same as Example 1, except that the homemade modified nano zinc oxide filler is replaced by original nano zinc oxide.

[0042] Comparative Example 2 Same as Example 1, except that the homemade modified carbon nanotube filler is replaced by original carbon nanotubes.

[0043] Comparative Example 3 Same as Example 1, except that the homemade modified graphene filler is replaced by original graphene.

[0044] Comparative Example 4 Same as Example 1, except that no self-extractable antifouling agent is added.

[0045] Antibacterial test: The experiment was conducted in accordance with the method of GB / T 21866-2008. Step 1: Prepare the eluent (3.5% NaCl solution), liquid culture medium NB (H2O1000ml, NaCl 5g, beef extract 5g, protein Chen 10g) and solid culture medium NA (NB 1000ml, agar 15g) for use. The pH value of the above solutions should be adjusted to between 7.0 and 7.2; Step 2: Sterilize the eluent, NB, NA, test tubes, pipette tips, glass dishes and centrifuge tubes at 121°C for 20 minutes; Step 3: Inoculate the refrigerated Staphylococcus aureus onto NA in the clean bench and activate it in a constant temperature incubator at 37°C for 24 hours; Step 4: Inoculate a small amount of activated bacteria into 5ml NB and culture it in a constant temperature desktop oscillator for 24 hours at 37°C and 220 rpm. ; Step 5. Clean the sample surface with 75% ethanol solution in a clean bench, rinse the residual alcohol with sterile distilled water, and sterilize by ultraviolet irradiation for 30 minutes; Step 6. Dilute the bacterial solution 10 times 4 times, add 100ul of the diluted bacterial solution to the sample surface, and cover the sample surface with a sterilized PE film so that the bacterial solution and the sample are in full contact; Step 7. Place the sample in a sterilized glass dish and culture it at 37°C for 24 hours; Step 8. Rinse the PE film and the sample surface with 8ml of eluent, take 200ul of the washing solution and inoculate it on the NA, spread it evenly with a coating rod, and place the NA in a constant temperature incubator at 37°C for 24 hours; Step 9. Count the colonies using the plate counting method.

[0046] Corrosion resistance test: VersaSTAT 4 electrochemical workstation and three-electrode system were used for testing. The steel sheet coated with the composite coating was placed at the bottom of the electrolytic cell. Saturated calomel electrode and nail electrode were used as the working electrode, reference electrode and auxiliary electrode respectively. A 3.5% NaCl solution was placed inside the electrolytic cell to fully immerse the coating. The parameters of the VersaSTAT 4 electrochemical workstation were set as follows: perturbation voltage 20mV sinusoidal voltage; start frequency 100000Hz; cut-off frequency 0.01Hz. The test time was one month, and the data was compared and studied, and the fitting analysis was performed using ZSimpWin software. Y o The smaller the value, the c The larger the value, the better the corrosion resistance.

[0047] Antifouling test: The steel sheet coated with the composite coating was placed in a natural river for 30 days to observe the number of organisms attached to the coating surface.

[0048] The test results are shown in the following table:

[0049] Test results: The test data show that the anti-corrosion composite coating prepared by adding self-made modified nano zinc oxide filler, self-made modified carbon nanotube filler, self-made modified graphene filler and self-extracted antifouling agent has excellent antibacterial and corrosion resistance, and has good avoidance to organisms.

[0050] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A corrosion-resistant marine anticorrosive composite coating, comprising 5-8 parts by weight of a corrosion inhibitor, 90-100 parts by weight of an epoxy resin, 10-20 parts by weight of an inactive diluent and 45-50 parts by weight of a curing agent, characterized in that: The composite coating also includes, by weight, 2-6 parts of a homemade modified nano zinc oxide filler, 0.5-1.5 parts of a homemade modified carbon nanotube filler, 5-8 parts of a homemade modified graphene filler, and 1-2 parts of a self-extractable antifouling agent.

2. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The preparation method of homemade modified nano zinc oxide filler is: Add n-butanol 6 times the mass of nano zinc oxide and isopropyl tri(dioctyl pyrophosphoryl) titanate 0.06 times the mass of nano zinc oxide into the reaction bottle, stir and mix for 5 minutes, add nano zinc oxide, heat to 40°C and stir for 2 hours, filter, vacuum dry the filter cake at 60°C to constant weight, grind and pass through a 2000 mesh sieve to obtain the filter cake; The preparation method of homemade modified carbon nanotube filler is: Concentrated sulfuric acid with a mass of 100 times the mass of carbon nanotubes and concentrated nitric acid with a mass of 200 times the mass of carbon nanotubes are sequentially added to the reaction bottle, stirred and mixed evenly, then carbon nanotubes are added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times the mass of carbon nanotubes and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, water rinsed the filter cake to pH = 7, and vacuum dried at 60°C to obtain hydroxylated carbon nanotubes; another reaction bottle is taken, purified water with a weight of 5 times the weight of carbon nanotubes and γ-aminopropyltriethoxysilane with a weight of 0.08 times the weight of carbon nanotubes are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated carbon nanotubes are added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried 3 times with water, rinsed with acetone twice, vacuum dried at 40°C to constant weight, ground and sieved through a 2000 mesh sieve to obtain; The preparation method of homemade modified graphene filler is: Concentrated sulfuric acid with a mass of 100 times that of graphene and concentrated nitric acid with a mass of 200 times that of graphene are added to the reaction bottle in sequence, stirred and mixed evenly, then graphene is added, heated to 65°C and stirred for reaction for 10 hours, filtered while hot, the filter cake is added to purified water with a volume of 200 times that of graphene and slurried for 10 minutes, filtered, repeated slurrying and filtration 4 times, the filter cake is rinsed with water to pH=7, and vacuum dried at 60°C to obtain hydroxylated graphene; another reaction bottle is taken, purified water with a weight of 5 times that of graphene and γ-aminopropyltriethoxysilane with a weight of 0.08 times that of graphene are added to the reaction bottle, stirred and mixed for 10 minutes, hydroxylated graphene is added under stirring, heated to an internal temperature of 75°C and stirred for reaction for 10 hours, cooled to 25°C, filtered, the filter cake is slurried and rinsed with water 3 times, rinsed with acetone twice, dried in vacuum at 40°C to constant weight, ground and sieved through a 2000-mesh sieve to obtain.

3. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The corrosion inhibitor is a powder mixture of sodium nitrite and potassium dihydrogen phosphate, sodium nitrite: potassium dihydrogen phosphate W / W=1 / 1.

4. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The epoxy resin is E44 bisphenol A type epoxy resin.

5. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The preparation method of the self-extractable antifouling agent is as follows: the dried shashaola chili is crushed in a crusher, added into ethanol with a volume 5 times the weight of the shashaola chili, heated to an internal temperature of 50°C, stirred and extracted for 12 hours, filtered, and the filtrate was concentrated under reduced pressure to dryness to obtain the self-extractable antifouling agent.

6. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The inactive diluent is a mixture of n-butanol and diethylene glycol dimethyl ether, with n-butanol: diethylene glycol dimethyl ether W / W=6:

4.

7. The corrosion-resistant marine anticorrosive composite coating according to claim 1, characterized in that: The curing agent is 650 polyamide curing agent, and the amine value of the curing agent is 220±20.

8. The preparation process of the corrosion-resistant marine anticorrosive composite coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add the inactive diluent to the reaction bottle in order according to the mixing ratio, add the corrosion inhibitor and the self-extractable antifouling agent in order under stirring, and heat to 50° C. to dissolve, to obtain a mixture 1; S2, adding the homemade modified nano zinc oxide filler, the homemade modified carbon nanotube filler and the homemade modified graphene filler to the mixed material 1 obtained in step S1 under stirring, and stirring for 10 minutes to make the mixture evenly dispersed to obtain a mixed material 2; S3, slowly adding the mixture 2 obtained in step S3 into E44 bisphenol A epoxy resin under stirring, stirring and mixing for 30 minutes to obtain a mixture 3; S4, adding a curing agent to the mixture 3 obtained in step S3 under vigorous stirring, mixing evenly, and standing to mature.

9. The process for preparing the corrosion-resistant marine anticorrosive composite coating according to claim 8, characterized in that: The standing and aging time in step S4 is 40 minutes.

Citation Information

Patent Citations

  • Nano-composite marine anti-fouling coating material and preparation method thereof

    CN102977744A

  • Hydrophobic nano composite ocean anti-staining coating and preparation method thereof

    CN103265869A

  • Graphene-containing marine anticorrosion antifouling coating and preparation method thereof

    CN103589282A

  • Zinc oxide surface modification method by titanate coupling agent

    CN103694743A

  • Water-based rust conversion and prevention paint

    CN104530855A

Cited By

  • Electronic component shell master batch and injection molding method of shell

    CN119931338A

  • Graphene-reinforced heavy-duty epoxy coating for marine environment

    CN121160180A